Intervensi China dalam Mediasi Perdamaian Arab Saudi dengan Iran - Canta Bayu Laksana; Peni Hanggarini (Universitas Al-azhar Indonesia, 2025)
This paper aims to analyze China’s intervention in mediating peace between Saudi Arabia and Iran. The discussion focuses on China's soft power strategy as a mediator between these two Middle Eastern countries, which have long experienced tense relations. This issue is considered significant, as the success of the mediation not only affects regional stability but also reflects shifting global power dynamics and highlights China's growing role in international geopolitics. The research adopts a qualitative method, employing Joseph Nye’s soft power theory as an analytical framework to understand how China builds its influence through non-coercive means, particularly economic cooperation and diplomacy. Data were collected through literature review and analyzed using descriptive qualitative techniques. The findings indicate that China’s success as a mediator is largely attributed to its economic diplomacy and neutral stance, which fostered trust from both parties. These results underscore the importance of soft power in expanding global influence and present a viable alternative to conflict resolution that does not rely on military force. This study contributes to the field of international relations and Middle Eastern geopolitics by emphasizing the necessity of strengthening non-coercive diplomacy as a means to maintain regional stability and build long-term peace.